Visualization of discontinuous vector field topology - Miftari, Egzon; Durstewitz, Daniel; Sadlo, Filip (IEEE transactions on visualization and computer graphics, 2024)
This paper extends the concept and the visualization of vector field topology to vector fields with discontinuities. We address the non-uniqueness of flow in such fields by introduction of a time-reversible concept of equivalence. This concept generalizes streamlines to streamsets and thus vector field topology to discontinuous vector fields in terms of invariant streamsets. We identify respective novel critical structures as well as their manifolds, investigate their interplay with traditional vector field topology, and detail the application and interpretation of our approach using specifically designed synthetic cases and a simulated case from physics.
Online veröffentlicht: 25. Oktober 2023
Gesehen am 16.08.2024